Práticas pedagógicas e a educação infantil: desafios e possibilidades - Morais, Patrícia Ferreira de (2014)
The present research aims at verifying and understanding the interaction between teacher s pedagogical practises in Early Childhood Education, their Further education and the feasibility of a new curriculum. The following research methods were used: qualitative research, participative research, field research, bibliography, document analysis, focus groups for collection of data and also a questionnaire to profile participants. Participants are teachers of Early Childhood Education at a confessional private school in São Paulo. As a result, it became quite clear that the educational universe has been through great changes. The conception of childhood has changed. Early childhood education is no longer based on the mere assistance of the child; it s rather an educational process which demands new attitudes towards the child s process of development. In this new scenario, the teacher is a mediator who bases their work on the concept of abilities in order to promote meaningful learning which must be useful to the child s personal and social life, promoting a humanistic formation. Therefore, the pedagogical practise can be seen as means of updating, innovating, enabling and contextualizing practises and the learning process. It should no longer stifle the spontaneity, creativity and genuineness which are a true part of the interactions with and among the children at school. In the presence of diverse theoretical and ideological trends and also of different practises, teachers are expected to have a critical and creative attitude towards this new perspective so that practice and theory go hand in hand. Naturally, teachers should do so with the help and assistance of the coordination and other managerial staff and also the institution, preferably in further educational meetings